Moral Character Education after COVID-19: An Interview - Curren, Randall; Barber, Zachary; Ryan, Richard (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2022)
This interview piece addresses the following questions: Does the COVID-19 pandemic offer any lessons for moral character education? Do the experiences of students, educators, and communities during the pandemic illustrate the importance of aspects of character education that may have been known but taken for granted? The three authors bring to this the perspectives of a philosopher of moral psychology and education (Curren, the interviewer), a clinical psychologist and co-founder of self-determination theory (SDT), a systematic approach in the psychology of motivation, development, and well-being (Ryan); and a moral theorist focused on mindfulness and virtue (Barber).